An Overview of the Literature on the Hexa-Helix Key Stakeholders Coopetition in Developing Responsible Tourism in Natural Tourism Parks - Rata Wijaya; Akhmad Saufi; Baiq Handayani Rinuastuti (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study examines the application of the Hexa-Helix coopetition framework in developing responsible tourism at Gunung Tunak Nature Tourism Park, Central Lombok. Using a qualitative descriptive-analytical approach, data were gathered through purposive and snowball sampling, in-depth interviews, field observations, and document analysis involving six stakeholder groups: government, academia, industry, community, media, and regulatory bodies. The findings reveal that responsible tourism is implemented through a co-management system that integrates the Triple Bottom Line dimensions—economic, social, and environmental sustainability—into tourism governance. The Hexa-Helix model fosters synergy by aligning diverse stakeholder roles, where cooperation and competition coexist to drive innovation, resource optimization, and competitiveness. Community empowerment programs, participatory decision-making, and policy institutionalization are identified as key drivers of sustainability. Practical strategies include capacity-building training, infrastructure improvement, and equitable benefit-sharing mechanisms, which strengthen both conservation outcomes and local livelihoods. Theoretically, this study advances the literature on sustainable tourism by embedding the concept of coopetition within the Hexa-Helix model, offering an adaptable framework for other destinations. Context-specific insights emphasize the critical role of local champions in bridging interests among stakeholders, ensuring long-term collaboration and resilience.